Chronic exertional compartment syndrome of the forearm: a systematic review. Issue 2 (1st February 2021) - Smeraglia, Francesco; Tamborini, Federico; Garutti, Leonardo; Minini, Andrea; Basso, Morena A.; Cherubino, Mario
Abstract : The aim of this systematic review is to understand which surgical procedure provides better results in terms of pain relief and function in the treatment of chronic exertional compartment syndrome (CECS) of the forearm. We searched Medline (PubMed), Web of Science, Embase and Scopus databases on 8 July 2020. Twelve studies were included in this review. We assessed the quality of the studies using the Coleman Methodological Score. Data on demographic features, operative readings, diagnostic methods, follow-up periods, type and rates of complications, survivorship of the procedure, return to sport activity, and outcome measures were recorded. In conclusion, compared to the other techniques, endoscopic fasciotomy delivers similar success rates and lower incidence of complications. Cite this article: EFORT Open Rev 2021;6:101-106. DOI: 10.1302/2058-5241.6.200107